2022
DOI: 10.1186/s12889-022-13974-4
|View full text |Cite
|
Sign up to set email alerts
|

To disclose or not: experiences of HIV infected pregnant women in disclosing their HIV status to their male sexual partners in Blantyre, Malawi

Abstract: Background HIV status disclosure is one of the pillars of success of the elimination of Mother to Child Transmission of HIV (eMTCT) program. However, there are challenges associated with it that limit full disclosure. Literature shows that for pregnant women in developing countries, who have been diagnosed with HIV, 16% to 86% disclose their status to their sexual partners. This study explored the experiences of newly diagnosed HIV-infected antenatal women in disclosing their HIV status to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…This nding on HIV status disclosure was lower than most studies from Sub-Saharan Africa, with disclosing HIV status with a partner ranging from 70% and 86.5% ( [50,6,[51][52][53][54] . Other African studies have found that HIV-infected women who had not disclosed their status did not do so due to the fear of abandonment by a male partner [55] and these women were less likely to use PMTCT services [56,57]. In a qualitative study in urban Kenya, HIV positive women who did not disclose their status [56] were found to be relatively new in their relationships and their employment status was also associated with non-disclosure of HIV-positive status.…”
Section: B Individual-level Stressorsmentioning
confidence: 99%
“…This nding on HIV status disclosure was lower than most studies from Sub-Saharan Africa, with disclosing HIV status with a partner ranging from 70% and 86.5% ( [50,6,[51][52][53][54] . Other African studies have found that HIV-infected women who had not disclosed their status did not do so due to the fear of abandonment by a male partner [55] and these women were less likely to use PMTCT services [56,57]. In a qualitative study in urban Kenya, HIV positive women who did not disclose their status [56] were found to be relatively new in their relationships and their employment status was also associated with non-disclosure of HIV-positive status.…”
Section: B Individual-level Stressorsmentioning
confidence: 99%
“…HIV-related stigma and discrimination can prevent women from seeking testing, treatment, and support services. Fear of disclosure, judgment, or rejection may lead to delayed diagnosis and reduced adherence to treatment, impacting overall health outcomes [60,61].…”
Section: Hiv Among Black Womenmentioning
confidence: 99%
“…Partner disclosure – the process of enlightening HIV status to a partner – is associated with improved antiretroviral therapy (ART) initiation, adherence, and retention in care among pregnant and postpartum women [ 2 ] and safe infant feeding practices [ 3 , 4 ]. Further, women’s partner disclosure can boost partner relationships, through male partner’s involvement in pregnancy [ 5 , 6 ], social support [ 7 ], HIV testing among male partners, and condom use among HIV sero-different partners [ 6 , 8 , 9 ] but evidence is inconsistent across settings [ 10 , 11 ]. Non-disclosure, on the other hand, can cause worry and stress among pregnant women [ 12 ] leading to sub-optimal engagement in antenatal care (ANC) [ 13 ] and ART services [ 12 , 14 , 15 ], virologic non-suppression [ 16 , 17 ] and infant feeding challenges [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Partner disclosure is difficult, more so during pregnancy [ 9 , 12 ]. Rates of partner disclosure among pregnant women living with HIV range from 30 to 93% (pooled estimate: 64%) across Africa [ 18 ], also being lower for HIV-seropositive status compared to HIV-negative status [ 10 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation